PENGARUH KNOWLEDGE SHARING DAN HARDSKILLTERHADAP KINERJA KARYAWAN PT. EJUKHA (PEMATANG GUBERNUR) - Lupi Dwi Sintri; Merta Kusuma (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
Employee performance in companies operating in the contracting, construction, and property sectors is shaped by multiple factors, notably knowledge sharing and hard skills. This study investigates the influence of knowledge sharing and hard skills on employee performance at PT. Ejukha, Pematang Gubernur. A quantitative research design with a descriptive approach was employed. The population was all employees of PT. Ejukha, with a total sample of 25 respondents selected through a census technique. Data were collected via questionnaires and analyzed using multiple linear regression. The analysis produced the regression equation Y=1.074+ 0.172X Box+0.750X Box. Knowledge sharing showed a positive and significant effect on employee performance (11.743, p = 0.047 ) while hard skills also had a positive and significant effect underline ( t = 2.269 , p = 0.033 ) Simultaneously, both variables significantly affected performance ( F = 22.505 , p < 0.001). The findings confirm that enhancing knowledge-sharing practices and improving hard skills can significantly strengthen employee performance. It is recommended that PT. Ejukha continue developing structured knowledge-sharing initiatives and targeted skill enhancement programs to sustain optimal performance outcomes. Keywords: employee performance, knowledge sharing, hard skills